Bone natural autofluorescence and confocal laser scanning microscopy: Preliminary results of a novel useful tool to distinguish between forensic and ancient human skeletal remains. (March 2017) - Capasso, Luigi; D'Anastasio, Ruggero; Guarnieri, Simone; Viciano, Joan; Mariggiò, Maria
Highlights: A novel dating method was developed using the autofluorescence of human bones. Endogenous fluorophores are present following the topographic distribution of the so-called Rouget–Neumann sheath. The intensity of the natural fluorescence in human bone decreases in a relationship to the antiquity of the samples. Abstract: The fast, high-throughput distinction between palaeoanthropological/archaeological remains and recent forensic/clinical bone samples is of vital importance in the field of medico-legal science. In this paper, a novel dating method was developed using the autofluorescence of human bones and the confocal laser scanning microscope as the means to distinguish between archaeological and forensic anthropological skeletal findings. Human bones exhibit fluorescence, typically induced by natural antibiotics that are absorbed by collagen, and provide secondary, exogenous fluorophores. However, primary natural fluorescence (or autofluorescence) caused by enigmatic endogenous fluorophores is also present as a micro-phenomenon, whose nature is still obscure. Here, we show that the endogenous fluorophores are mucopolysaccharides of the Rouget–Neumann sheath and, more relevant, that the intensity of the natural fluorescence in human bone decreases in a relationship to the antiquity of the samples. These results suggest that the autofluorescence of bone is a promising technique for the assessment of skeletal remains that may be potentially of medico-legal interest. A larger study is proposed to confirm these findings and to create a predictive model between the autofluorescence intensity and the time since death.